Altered functional brain states predict cognitive decline 5 years after a clinically isolated syndrome. (October 2022) - Koubiyr, Ismail; Broeders, Tommy AA; Deloire, Mathilde; Brochet, Bruno; Tourdias, Thomas; Geurts, Jeroen JG; Schoonheim, Menno Michiel; Ruet, Aurélie
Background: Cognitive impairment occurs in the earliest stages of multiple sclerosis (MS) together with altered functional connectivity (FC). Objective: The aim of this study was to investigate the evolution of dynamic FC states in early MS and their role in shaping cognitive decline. Methods: Overall, 32 patients were enrolled after their first neurological episode suggestive of MS and underwent cognitive evaluation and resting-state functional MRI (fMRI) over 5 years. In addition, 28 healthy controls were included at baseline. Results: Cognitive performance was stable during the first year and declined after 5 years. At baseline, the number of transitions between states was lower in MS compared to controls ( p = 0.01). Over time, frequency of high FC states decreased in patients ( p = 0.047) and increased in state with low FC ( p = 0.035). Cognitive performance at Year 5 was best predicted by the mean connectivity of high FC state at Year 1. Conclusion: Patients with early MS showed reduced functional network dynamics at baseline. Longitudinal changes showed longer time spent in a state of low FC but less time spent and more connectivity disturbance in more integrative states with high within- and between-network FC. Disturbed FC within this more integrative state was predictive of future cognitive decline.